Perlindungan Konsumen Muslim terhadap Produk Pangan Daging Non Kemasan melalui Jaminan Produk Halal - Nurani, Intan; Zakky, Moh; Lubis, Efridani (Jurnal Hukum Jurisdictie, 2021)
Related to the validity of non-packaged meat food products, Law No. 8 of 1999 on Consumer Protection only stipulates that business actors are prohibited from producing and/or trading goods and/or services that do not follow the provisions of halal production, as stated "halal" contained in the label. Regarding the necessity of halal information in non-packaged meat food products, it can be seen in Law No. 33 of 2014 on Halal Product Guarantee, which includes "products" in the Halal Products Act are goods and / or services related to food, beverages, drugs, cosmetics, chemical products, biological products, genetic engineering products, and used goods used, used, or utilized by the community. While what is meant by halal products is products that have been declared halal in accordance with Islamic sharia. The Halal Product Law has clearly stipulated that products entered, circulated, and traded in the territory of Indonesia must be halal certified. So basically, if the product sold is halal, then it must be halal certified. Consumer protection law today gets quite attention because it concerns the rules for the welfare of society, not only the community as consumers who get protection, but business actors also have the same right to protection, each has rights and obligations. The government plays a role in regulating, supervising, and controlling so as to create a conducive system that is related to each other, thus the goal of the welfare of society at large can be achieved. In healthy business activities there is a balance of legal protections between consumers and producers. The absence of balanced protection causes consumers to be in a weaker position even if the product produced by the manufacturer is a limited type of product, it will certainly harm the consumer. Haram food has been detailed in the Quran, while halal food is not explained, which is why in Indonesia it is regulated about halal certification with the aim that the interests of consumers can be protected.